The Rhythem of Prose in Beyhaqi's History - قدسیه رضوانیان; مرضیه حقیقی (مطالعات زبانی و بلاغی)
Beyhaqi's history is one of unique texts in Persian Literature that has remained unrepeatable and unimitable because of it's mixing with music substantially. The history mixed with art avant â gard art. Beyhaqi's history, although, is the production of combination of many elements, the role of music is undeniable in it's outstanding. Rhythmic prose is seen evidently in Khaje â Abdollah â e â Ansari's Monajat Nameh and Sa'di's Golestan and other rhymed prose, that in there, rhyme and other abstract and verbal elements promote prose to poetry. But Beyhaqi's history isn't like them although it also uses from these elements. Rhythm in Beyhaqi's history derives from the music of works and it's connection with the structure of his text, that is, that a metre and order is in the western modern poem and Shamloo's poetry. This paper deals with Beyhaqi's history in this view point that is harmonic that like modern prose poem and the most important elements which have role of generation of music like: the music of words, the reapatition of word and voice, the music application of adverb, the word of "Ra", rhythmic composition, the syntagmatic of opposition elements, the role of simile, and the metathesis of components of qsentence.